Branding Design and Trademark Registration for Micro, Small dan Medium Enterprises (MSMEs) - Ida Nuraini; Happy Febrina Hariyani (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The introduction of a product through a brand or brand that is easily remembered and recognized by consumers will have an impact on the development of the business.